2008
DOI: 10.18011/bioeng2008v2n1p37-44
|View full text |Cite
|
Sign up to set email alerts
|

Características Do Caldo De Cana E Sua Influência Na Estabilidade Da Bebida

Abstract: RESUMOO Brasil é considerado o maior produtor mundial de cana-de-açúcar, e as regiões Nordeste e Sudeste são as maiores produtoras nacionais. A pesquisa objetivou determinar os principais constituintes do caldo de cana tais como água, sacarose, açúcares redutores, proteína, polissacarídeos totais, dextrana, cinzas e minerais (fósforo, potássio, cálcio e magnésio), além de analisá-lo físico-quimicamente (pH, acidez, sólidos solúveis, relação Brix/Acidez ("ratio"), teor de ácido ascórbico e atividade da pectines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Gallo (1989) and Kaufmann (2021) says that the pH of the sugarcane must be between 5.0 and 5.5. Other authors (Prati;Camargo, 2008;Rodrigues et al, 2019) found pH values between 5 and 6.17 and stated that these are satisfactory. Analyzing the pH results for the filtered juice, these are in the cited ranges, but analyzing the results for the decanted juice, juice 2 are not in the ranges.…”
Section: Discussionmentioning
confidence: 88%
“…Gallo (1989) and Kaufmann (2021) says that the pH of the sugarcane must be between 5.0 and 5.5. Other authors (Prati;Camargo, 2008;Rodrigues et al, 2019) found pH values between 5 and 6.17 and stated that these are satisfactory. Analyzing the pH results for the filtered juice, these are in the cited ranges, but analyzing the results for the decanted juice, juice 2 are not in the ranges.…”
Section: Discussionmentioning
confidence: 88%
“…As principais características da garapa são a sua viscosidade e a coloração escura. Basicamente, é composta de água e açúcares, tais como: sacarose; frutose; e glucose (PRATI; CAMARGO, 2008).…”
Section: Introductionunclassified
“…O caldo de cana possui alta concentração de açúcares e baixa acidez, por isso é muito susceptível a deterioração principalmente por leveduras que levam à sua fermentação. Apesar disso, a RDC 12/2001 estabelece padrões microbiológicos apenas para coliformes 45ºC e Salmonella spp (Brasil, 2001;Prati & Camargo, 2008). A higienização no preparo visa além da preservação da palatabilidade e qualidade microbiológica dos alimentos, um produto que tenha qualidades nutricionais e sensoriais adequados não oferecendo riscos à saúde.…”
Section: Introductionunclassified